Optimizing Toxic Chemical Removal through Defect‐Induced UiO‐66‐NH2 Metal–Organic Framework. Issue 63 (24th October 2017) - Peterson, Gregory W.; Destefano, Matthew R.; Garibay, Sergio J.; Ploskonka, Ann; McEntee, Monica; Hall, Morgan; Karwacki, Christopher J.; Hupp, Joseph T.; Farha, Omar K.
Abstract: For the first time, an increasing number of defects were introduced to the metal–organic framework UiO‐66‐NH2 in an attempt to understand the structure–activity trade‐offs associated with toxic chemical removal. It was found that an optimum exists with moderate defects for toxic chemicals that react with the linker, whereas those that require hydrolysis at the secondary building unit performed better when more defects were introduced. The insights obtained through this work highlight the ability to dial‐in appropriate material formulations, even within the same parent metal–organic framework, allowing for trade‐offs between reaction efficiency and mass transfer. Abstract : The effect of defects within the UiO‐66‐NH2 structure were evaluated with respect to toxic chemical removal. It was found that more defects resulted in increased reactivity towards nerve agents, but an optimum exists for chemicals requiring linker functionality for removal (see scheme).